2022
DOI: 10.1093/ndt/gfac024
|View full text |Cite
|
Sign up to set email alerts
|

The level of urinary C4d is associated with disease progression in IgA nephropathy with glomerular crescentic lesions: a cohort study

Abstract: Background Positive glomerular C4d staining, representative of lectin pathway activation, has been proven to be associated with unfavorable outcomes in IgA nephropathy (IgAN). Our previous study suggested that urinary C4d correlated positively with an increase in crescents. While the relationship between urinary C4d and disease severity and progression remains unelucidated. Methods In this study, we enrolled 168 patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…, 30 2022 C4d Spain Adult 34 IHC 34 46 85 (72–101) 2.9 (0.9–3.7) Wang et al. , 11 2022 C4d China Adult 34 urine, ELISA 34 56 33.4 (16.2–61.7) 3.5 (1.7–5.1) Itami et al. , 31 2020 C3, C4, C4d, C1q, C5b9, MBL, MASP1/3, MASP2, properdin, factor B Japan Adult 132 IF 52 55 61.1 (9.7–162) 1.3 (0.04–7.8) Yang et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 30 2022 C4d Spain Adult 34 IHC 34 46 85 (72–101) 2.9 (0.9–3.7) Wang et al. , 11 2022 C4d China Adult 34 urine, ELISA 34 56 33.4 (16.2–61.7) 3.5 (1.7–5.1) Itami et al. , 31 2020 C3, C4, C4d, C1q, C5b9, MBL, MASP1/3, MASP2, properdin, factor B Japan Adult 132 IF 52 55 61.1 (9.7–162) 1.3 (0.04–7.8) Yang et al.…”
Section: Resultsmentioning
confidence: 99%
“…, 30 2022 Lectin pathway Higher levels in patients with M1, E1, T1-2, C1-2 classes c Wang et al. , 11 2022 No relationship with MEST-C classes a Itami et al. , 31 2020 Associated with T1-2 class a Yang et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma exchange therapy has been proven bene cial for patients with ANCA-associated vasculitis or crescentic glomerulonephritis caused by anti-GBM antibodies [19,20]. However, Wang et al suggested that plasma exchange therapy does not improve the prognosis of patients with crescentic IgA nephropathy on top of conventional immunosuppressive therapy [21]. Within our follow-up cohort, a total of 16 patients underwent combination therapy involving plasma exchange, glucocorticoids, and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 83%
“…32 In patients with IgA nephropathy, urinary C3a and C5a levels, as well as several inflammatory factors, were increased and related to impaired kidney function and/or disease progression. 33,34 Inflammatory cells residing in the local glomerular were frequently observed in IgA nephropathy, 35 indicating active inflammation in the glomeruli. 36,37 Taking these clues together, we speculated that in addition to the MAC, the inflammation induced by complement activation might also take part in kidney injury and progression of IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%